Advancing Production Management through Industry 4.0 Technologies - Shih-Chih Chen; Istiqomah Yati; Eiser Aaron Beldiq (Pandawan Sejahtera Indonesia, 2024)
The development of Industry 4.0 technologies has brought significant changes to various sectors, including production management. In increasingly complex production environments, the adoption of Industry 4.0 technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics has become crucial for enhancing the efficiency and effectiveness of production pro- cesses. This study aims to explore how Industry 4.0 technologies can be applied in production management to optimize operational performance and reduce re- source wastage. The research employs a quantitative approach with data analysis obtained from case studies of manufacturing companies that have implemented Industry 4.0 technologies. Data collection was conducted through surveys and interviews with production managers, along with the analysis of operational per- formance reports. The results indicate that the implementation of Industry 4.0 technologies significantly improves production efficiency, accelerates response times to market demand changes, and reduces operational costs. These findings suggest that integrating Industry 4.0 technologies into production management can be an effective strategy for addressing the challenges of global competi- tion and changing market dynamics. This research contributes to the production management literature by offering insights into the positive impact of adopting Industry 4.0 technologies in operational contexts. The results are expected to serve as a reference for practitioners in developing more adaptive and innovative production strategies in the digital era.